Efforts in Improving Squat Style Long Jump Skills Using the Rubber Exercise Method for Grade VIII A of MTSN 1 Seluma - Oksandi Sanjaya; Deffri Anggara; Azizatul Banat (Penerbit Jurnal Indonesia, 2022)
This study aims to improve students' learning skills with squat style long jump using the Rubber media in grade VIII A of MTs Negeri 1 Seluma in Academic Year of 2021/2022. In accordance with the problems and research objectives, this study used a class action research method with a total of 30 subjects. The population is grade VIII A of MTs Negeri 1 Seluma. The research instrument used in this study was an observation sheet or observations and documentation. The researcher analyzed the data after the incoming student scores, then determined the classical value completeness and the students' average score. After being implemented, it was proven that the number of students whose skills in using tools such as blades and hanging balls increased more and more, namely in the first cycle, there were 20 students who could perform the squat style long jump with 75% classical completeness, in the second cycle it increased to 30 students. with classical completeness of 100%. Thus it can be concluded that there is an increase in the squat style long jump skill after applying the training method with rubber media to grade VIII A students of MTs Negeri 1 Seluma.